ANALYSIS OF FACTORS DETERMINING LAND REGISTRATION COSTS AND THEIR IMPACT ON AFFORDABILITY FOR LOW-INCOME COMMUNITIES - Gunawan Widjaja (Adisam Publisher, 2025)
This study aims to analyse the factors that determine land registration costs and their impact on the affordability of registration services for low-income communities in Indonesia. The method used is a literature review, examining regulations, scientific studies, policy reports, and documentation related to land administration and registration costs. The results of the study show that land registration costs are influenced by national regulations, technical measurement costs, complex bureaucracy, and the existence of unofficial fees that increase the burden on the community. High costs and complicated procedures are major obstacles for low-income communities in obtaining land certificates, thereby negatively impacting their access to legal certainty, asset protection, and economic opportunities. This study recommends the need for simplified procedures, cost transparency, supervision of illegal levies, as well as subsidies and the use of digital technology to improve the affordability of land services for the poor.